Efeito de micorrizas e da fertilização no crescimento de mudas de campomanesia xanthocarpa (Mart.) O.Berg., produzidas em diferentes substratos - Dalanhol, Samanta Jaqueline [UNESP]; Nogueira, Antonio Carlos; Gaiad, Sergio; Kratz, Dagma (Universidade Federal de Santa Maria, 2017)
Due to the need for recovery of degraded areas and permanent preservation areas, the planting of native species in Brazil increased and consequently there was an increase in demand for seedlings. Thus, in order to produce seedlings Campomanesia xanthocarpa with higher quality, the aim of this study was to evaluate the effect of arbuscular mycorrhizal fungi (AMF) inoculation, fertilization and substrate composition on growth of seedlings of this species. The experiment was conducted at Embrapa Florestas (Colombo, PR). Seedlings after germination in vermiculite were transplanted to plastic pots (100 cm3) containing substrates based in vermicompost and rice husk and commercial substrate base pine bark. These substrates were tested with and without mycorrhizal inoculation and the presence and absence of manuring. Analyzed the physico-chemical properties of substrates formulated and at 180 days, were evaluated height, diameter, aggregation of roots to the substrate, shoot dry biomass, root dry biomass, the relationship between height and diameter and Dickson quality index. Means were compared by Tukey test (5%). Inoculation with AMF did not influence the growth of seedlings, while the interaction between substrates and fertilization was significant for most variables. The lack of response to AMF was probably due to high concentrations of phosphorus in these substrates. Fertilization had great effect on seedling growth, probably due to the reduced dimensions of the seeds that consumes all the reservation during the germination process. It was concluded that the substrate-based vermicompost and rice husk in the proportion of 30/70, can be used in the production of seedlings of this species. This substrate can replace the commercial base pine bark, where the seedlings showed reduced growth, for most variables.
Effect of mycorrhizae and fertilization on growth seedlings of campomanesia xanthocarpa (Mart.) O.Berg., produced in different substrates
Keywords: Arbuscular mycorrhizal fungi; Carbonized rice husk; Guabiroba; Vermicompost